Having trouble with this question. Usually i'd have to see examples first and rep it out but time ran out of class and i guess we couldn't see them. He gaves us tons of notes though but i'm not really sure if i'm doing it right. 1. The problem statement, all variables and given/known data for g(t) = 3t-2, determine each of the following. (the -1 is an inverse..) a. g -1 (-2) b. g -1(a+1) - g -1(a) 2. Relevant equations 3. The attempt at a solution Here's what i did with the g -1(-2) g(t)=3t-2 t=3g(t)-2 (t-2)/3=g(t) (-2-2)/3 = -4/3 I have no idea how to do the next one though. Well yea i do but it's probably completely wrong.